PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DALAM PENYALAHGUNAAN KEWENANGAN YANG MERUGIKAN KEUANGAN NEGARA - Aru Diba Al-hafidz; Edi Saputra Hasibuan; Widya Romasindah Aidy (JOURNAL OF LAW AND NATION, 2023)
This research is motivated to analyze a criminal act of corruption that abuses authority by government agencies and/or officials in making decisions and/or actions in government administration that are carried out by exceeding authority, and/or acting arbitrarily. Corruption is a form of extra ordinary crime problem where the actions of corruption committed not only affect human life as the category of extra ordinary crime. The purpose of this study is to find out how the criminal responsibility of perpetrators who abuse authority because of position to benefit themselves and harm the State. The research method used is a normative research method with a statutory approach and a case approach. The types and sources of legal materials used are primary, secondary, and tertiary materials using the collection of legal materials. The results obtained in the conclusions and suggestions of this study, Law enforcement against criminal acts of corruption that harm state finances pay attention to the elements of legal certainty, expediency, and justice. In general, the implementation of law enforcement is carried out in two ways, namely preventive and repressive. Acts of abuse of authority that can harm state finances against perpetrators of criminal acts must also pay attention to legal impunity (impunity), not affecting the running of legal processes when associated with the authority of perpetrators of corruption crimes as regional officials because equality before the law must work, as one of the fundamental principles of a state of law.